2018
DOI: 10.1177/0022487118806484
|View full text |Cite
|
Sign up to set email alerts
|

Exceeding Expectations: Teachers’ Decision Making Regarding Aboriginal and Torres Strait Islander Students

Abstract: Although Indigenous and non-Indigenous teachers, administrators, and educational policy makers have made efforts to improve Indigenous educational outcomes, slow progress limits the opportunities available to Indigenous learners and perpetuates social and economic disadvantage. Prior Canadian studies demonstrate that some teachers attribute low ability and adverse life circumstances to Indigenous students, possibly influencing classroom placement. These findings were the catalyst for an Australian-based study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Indigenous students are over represented within special education programs (DiGiacomo, Davidson, Abbott, Delaney, Dharmendra, McGrath, and Vasquez 2013;Sweller, Graham, and Van Begen 2012), and are more likely to face inequities than their non-Indigenous peers (Francis, Mill, & Lupton 2017;Ford 2013). Studies demonstrate that teachers have lower expectations of Indigenous students than their non-Indigenous peers (Riley, 2018(Riley, , 2012Dandy, Durkin, Barber, and Houghton 2015;Rubie-Davies, Hattie and Hamilton 2006). Indigenous scholars claim that teachers' deficit perceptions stem from a history of exclusionary practices and policies, ensuring that Indigenous peoples remain largely unseen within the educational environment (Herbert 2006;Sarra 2011;Nakata 2007), and that until these inequities are exposed, a gap between the achievement of Indigenous and non-Indigenous students will remain.…”
Section: Introductionmentioning
confidence: 99%
“…Indigenous students are over represented within special education programs (DiGiacomo, Davidson, Abbott, Delaney, Dharmendra, McGrath, and Vasquez 2013;Sweller, Graham, and Van Begen 2012), and are more likely to face inequities than their non-Indigenous peers (Francis, Mill, & Lupton 2017;Ford 2013). Studies demonstrate that teachers have lower expectations of Indigenous students than their non-Indigenous peers (Riley, 2018(Riley, , 2012Dandy, Durkin, Barber, and Houghton 2015;Rubie-Davies, Hattie and Hamilton 2006). Indigenous scholars claim that teachers' deficit perceptions stem from a history of exclusionary practices and policies, ensuring that Indigenous peoples remain largely unseen within the educational environment (Herbert 2006;Sarra 2011;Nakata 2007), and that until these inequities are exposed, a gap between the achievement of Indigenous and non-Indigenous students will remain.…”
Section: Introductionmentioning
confidence: 99%
“…The literature recognizes the challenge of 21st Century teacher education programs to equip prospective teachers with the necessary skills and capacities to successfully and equitably meet the diverse needs of Indigenous students in public school classrooms (Riley, 2019). According to some scholars, the refusal on the part of educators to contribute actively to issues of decolonization constitute acts of willful denial through avoiding uncomfortable and difficult thoughts and actions (McLaughlin & Whatman, 2015;Riley & Pidgeon, 2019).…”
Section: Contextmentioning
confidence: 99%
“…However, such programs must first aim to raise teacher candidates' critical consciousness by providing opportunities for them to thoughtfully and reflectively consider their biased and distorted beliefs respecting racial identity and inequity (Lewis, 2018). As an example, by incorporating Critical Race Theory (CRT) into teacher education programs of study, teacher candidates can benefit from better understanding how mainstream education practices can have adverse implications on Indigenous students' beliefs and epistemologies (Riley, 2019). This would appear to be especially relevant when one considers that teacher candidates generally prefer to teach students with similar backgrounds as their own and have lower professional and academic expectations for diverse students (Andrews & Gutwein, 2017).…”
Section: Contextmentioning
confidence: 99%
“…Connections are also drawn between these teacher expectations and attribution theory, wherein preexisting beliefs about groups of students change the way in which behaviors of those students may be interpreted. For example, a teacher who believes that Indigenous students will have behavioral issues may be more likely to attribute poor behavior to the student and their ethnic background rather than to situational factors (Riley & Ungerleider, 2012). Research has also shown that it is difficult for teachers from dominant groups to understand the issues facing their Indigenous students, which can exacerbate these effects (Tompkins, 2002).…”
Section: Social Behaviormentioning
confidence: 99%